Biomechanical indicators of difference in techniques of jump shots in the modern basketball - Novak, M.; Galic, M.; Otkovic, P.; Kasovic, M.; Zvonar, M. (Croatian Sports Medicine Journal, 2015)
The main goal of this research was to prove the difference in performances of the jump shot after movement and passed ball using two different techniques of stopping, one-touched and two-touched. One examinee, member of Croatian national team participated in this research. It included: the time of shot, the least value of the center of gravity of the body, the most value of the center of the gravity of the body, time of achieving the least value of the center of the gravity, time and average speed of the movement of the center of the gravity of the body from the least to the most value, passed distance of the center of gravity of the body horizontally. Examinee was recorded with six cameras. Recorded videos were edited using only SIMI Motion program package and received results with Statistica for Windows. The results showed that there is the statistically important difference in stopping techniques of basketball jump shot in the least and the most value of the center of the gravity of the body, the time of achieving the least value, the time difference between the least and the most value and the passed distance of the center of the gravity of the body horizontally. the analysis of obtained results gave us a conclusion that there is not statistically valuable time difference in performances of the jump shot and ,as well, the average speed difference from obtaining the least to the most value of the center of the gravity of the body.